Surface analysis of marine sulphate-reducing bacteria exopolymers on steel during biocrrosion using x-ray photoelectron spectoscopy - Sahrani, Fathul Karim; Aziz, Madzlan; Ibrahim, Zaharah; Yahya, Adibah (Universiti Kebangsaan Malaysia, 2008)

(untitled)
The aim of this study was to determine the surface chemistry during biocorrosion process on growth and on the production of exopolymeric substances(EPS)in batch cultures of mix-strains of marine sulphate-reducing bacteria (SRB) isolated from Malaysian Shipyard and Engineering Harbour, Pasir Gudang. The EPS and precipitates were analyzed by X-ray photoelectron spectroscopy (XPS). The XPS results indicate that Fe(2p 3/2)spectrum for iron sulphide can be fitted with Fe(II) and Fe(III) components,both corresponding to Fe-S bond types.The absence of oxide oxygen in the O(1s) spectrum and Fe(III)-O bond types in the Fe(2p 3/2) spectrum supports the conclusion that iron sulphides are composed of both ferric and ferrous iron coordinated with monosulphide and disulphide.